(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article offers an in-depth analysis of the capital-raising activities of commercial banks through the issuance of securities, drawing on theories of financial markets and corporate finance. The literature review examines the research of foreign and domestic scholars on increasing bank capital, including the motives for issuing shares and bonds. The article also compares the securities-related activities of Hamkorbank and Ipoteka-Bank for the period from 2023 to 2025, based on statistical data. The analysis shows the volume of share issuance of Hamkorbank and Ipoteka-Bank using graphs and tables. The conclusion offers recommendations for enhancing the capital-raising strategies of banks based on the findings.